THE LIME FLUID (Citrus aurantifolia) ABILITY of REDUCTION AGAINST HEAVY METALS in MUSSEL (Meretrix meretrix) KEPAH - Dita Natalia Purba; Mirna Ilza; Edison ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this research is to lower the levels of heavy metals found inthe mussel kepah by soaking with lime fluid which is containing citric acid. Themethod of this research was by using the experimental method. The design of thisresearch was the Complete Random Design (RAL) of a factorial pattern bytreatments of concentrations of 0% (C0), 15% (C15), 25% (C25), 35% (C35) andtreatments of 20 minutes (M20), 30-minute (M30) and 40 minutes (M40) longsoaking with three times repetitions. The results showed that the highest intensityof reduction of heavy metals of Pb, Zn and Cd are presented in limeconcentrations of 35% for 40 minutes long of soaking, produce results 53,53%,58.75% and 83,43% of reductions. A solution of lime was able to reduce heavymetals Pb, Zn and Cd but does not affect the value of the texture of the flesh ofmussel kepah. Soaking with lime fluid in a concentration of 0% for 20 minutes isthe best treatment based on organoleptik parameter, which the value of the view in(8.63) has a characteristic of bright, clear, very clean of flesh of mussel kepahwhich flavor and aroma is typical as clam kepah. The value of the texture in(8.31) has a characteristics of very gentle and not harsh of flesh of mussel kepah.The value of aroma in (8.68) has a characteristics of clear, bright, very interestingand very clean of flesh of mussel kepah, and the value of flavor in (6.09) has acharacteristic of typical flavor of mussel mixed with other flavors.Key words: ability of reduction, heavy metal, mussel kepah, concentration,soaking